Executive functions and emotion regulation relationship of suicidal ideation in children with ADHD (Annals of Medical Research, 2023)
Aim: There is evidence that suicidal thoughts are increased in attention deficit/hyperactivity disorder (ADHD). The aim of this study is to investigate the relationship between executive function (EF) deficits and emotion regulation negativity/lability (ERNL) in children with ADHD who reported suicidal ideation.Materials and Methods: This study was conducted in children aged 8-12 years with ADHD. Thirty-eight cases (ADHD + SI) with suicidal ideation and 41 cases without suicidal ideation (pure ADHD) were included in the study. Participants completed using the Children's depression inventory (CDI), the Screen for child anxiety-related emotional disorders (SCARED), the Behavior rating inventory of executive function (BRIEF) and the Emotion regulation checklist (ERC).Results: A significant difference was found between the 3 groups in terms of EF deficits and ERNL, CDI and SCARED. BRIEF subcomponents; there was a significant difference between inhibit, emotion control, monitor and behavior regulation index.Conclusion: Suicidal ideation is an important psychiatric health problem. Recognizing suicidal ideation in children; It can be effective in preventing suicidal behavior. Cognitive features such as EF deficits and ERNL may contribute negatively to suicidal ideation, especially in children with ADHD.